Mobilization strategies in minimizing pressure injuries in patients in the hospital setting (Research, Society and Development, 2022)
Objective: Need for knowledge about the mobilization strategies used to minimize the emergence of pressure injuries in patients confined to the hospital bed. Method: this study is a systematic review, in which eligibility criteria based on the PICO strategy were used, which included randomized clinical trials, which contained titles that addressed "pressure injuries" and/or "mobilization" Results: The selection process identified 1076 studies. After full reading and exclusion of duplicates and screening abstracts, 229 studies were selected. Among these, 15 scientific articles met the inclusion criteria. All studies pointed to pressure injuries as complication or adverse effect related to immobilization and prolonged hospitalization. Conclusion: Evidence shows that early mobilization is a safe technique with positive short and long-term results. in the ICU.